Analysis of elemental composition of Fe1‐xNix and Si1‐xGex alloy thin films by electron probe microanalysis and micro‐focus X‐ray fluorescence. (21st June 2020) - Hodoroaba, Vasile‐Dan; Terborg, Ralf; Boehm, Stephan; Kim, Kyung Joong
Abstract : The present study reports on results of analysis of the elemental composition of thin films by electron probe microanalysis with energy dispersive (ED‐EPMA) X‐ray spectrometry in conjunction with the dedicated thin‐film analysis software package Stratagem and by X‐ray fluorescence in its version with a micro‐focus X‐ray fluorescence (μ‐XRF) source attached to a scanning electron microscope (SEM). Two thin‐film systems have been analyzed: Fe1‐x Nix on silicon wafer and Si1‐x Gex on Al2 O3 substrate, in both cases the layers being grown to a thickness of about 200 nm by ion beam sputter deposition. Samples of five different atomic fractions have been produced and analyzed for each thin‐film system. Moreover, reference samples with certified elemental composition and thickness have been also available. This study is part of an interlaboratory comparison organized in the frame of standardization technical committee ISO/TC 201 "Surface chemical analysis." Two laboratories have been analyzed by ED‐EPMA (one laboratory standardless and one laboratory using both standardless and with standards variants) and one laboratory by μ‐XRF (standardless and with standards). All the elemental compositions obtained with different methods are in very good agreement for the complete two sets of five samples each.